SISTEM INFORMASI MONITORING EKSTRA KURIKULER SMP NEGERI 7 KOTA JAMBI BERBASIS WEB: Extracurricular;MySQL;Registration Process;Website. - Puad, Lailyn; Limia Budiarti, Rike; Prisdawarti, Yuli (JURNAL AKADEMIKA, 2022)
The extracurricular system at SMP Negeri 7 Jambi City which is currently running is still manual, that is, by means of every activity announcement, it is still notified or delivered in the school wall or directly on the school field and notification via WhatsApp group. The management of extracurricular activities makes the academic section of students experience internal problems which will make the process of managing extracurricular activities take a long time. The method used in making this system by means of data collection, system planning, system analysis, system design and database. The system built on this website uses the PHP programming language and MySQL database. The input needs on the Extracurricular Website of SMP Negeri 7 Jambi City are extracurricular data, student data, and registration data. Process requirements needed are: Login Process, Registration Process, and input, edit, and delete processes. The output data produced is in the form of information that will be attached, including: registration activity reports. The purpose of making this Job Training is the creation of an extracurricular website for SMP Negeri 7 Jambi City. With the existence of a new system that has been designed and created by researchers, it can help facilitate the parties involved in developing extracurricular activities effectively.